Mechanical and electric friction properties of Poly(methyl methacrylate) – Nitrocellulose blend polymer for triboelectric nanogenerators - Nguyen Thi Thuy, Duong; Le Thi Thanh, Tam; Tung, Doan T.; Nguyen Tuan, Dung; Nguyen Anh, Duc; Ngo Thanh, Dung; Phan Ngoc, Hong; Le Trong, Lu; Phan Ngoc, Minh (Communications in Physics, 2024)
In this study, nitrocellulose - polymethyl methacrylate (NC/PMMA) blend film as a positive triboelectric material for triboelectric nanogenerator (TENG) with controlled flexibility was successfully synthesized by varying the PMMA content in the polymer blend. The combination of NC and PMMA reduced the limitations of the individual component materials with improved mechanical properties such as tensile strength, elastic modulus and elongation at breaking point. The TENG fabricated from NC/PMMA as a positive friction layer paired with fluorinated ethylene propylene (FEP) or polytetrafluoroethylene (PTFE) as a negative friction layer demonstrates a high peak to peak voltage output of 234 V at low frequency and with an actuation force of 10 N. The open circuit triboelectric voltage value maintains 91% durability after 26200 click-release cycles. This work provides a potential approach to simultaneously improve the electrical and mechanical properties of triboelectric materials, promoting the possibility of practical applications of TENG.